2015
DOI: 10.3389/fnut.2015.00020
|View full text |Cite|
|
Sign up to set email alerts
|

Warm Ambient Temperature Decreases Food Intake in a Simulated Office Setting: A Pilot Randomized Controlled Trial

Abstract: BackgroundWe hypothesized that exposure to temperatures above the thermoneutral zone (TNZ) would decrease food intake in young adults in a sedentary office environment over a 2-h period.MethodsParticipants wearing standardized clothing were randomized to perform routine office work in the TNZ, considered control (19–20°C), or above the TNZ considered warmer (26–27°C) using a parallel-group design (n = 11 and 9, respectively). Thermal images of the inner canthus of their eye and middle finger nail bed, represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 30 publications
1
21
2
Order By: Relevance
“…In our previous study, after control for thermal condition, gender, and BMI, the participants’ peripheral temperature was significantly associated with caloric intake ( P = 0.002), suggesting a mediating effect . The results of the present study did not suggest peripheral temperature as a mediating factor.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…In our previous study, after control for thermal condition, gender, and BMI, the participants’ peripheral temperature was significantly associated with caloric intake ( P = 0.002), suggesting a mediating effect . The results of the present study did not suggest peripheral temperature as a mediating factor.…”
Section: Discussioncontrasting
confidence: 59%
“…In our previous study, after control for thermal condition, gender, and BMI, the participants' peripheral temperature was significantly associated with caloric intake (P = 0.002), suggesting a mediating effect (18).…”
Section: Discussionmentioning
confidence: 82%
“…In a landmark 1984 study 1 , Roger Ulrich, a pioneer in health-care design research now at Chalmers University of Technology in Gothenburg, Sweden, found that people recovering from surgery in hospital rooms with views of nature needed shorter stays and fewer doses of strong pain medication than did those in rooms looking onto a brick wall. Others have reported that certain kinds of artificial light can improve sleep and reduce depression and agitation in people with Alzheimer's disease 2 ; that higher air temperatures seem to curb calorie consumption 3 ; that employees take more sick leave when they work in open-plan offices 4 ; and that children in daylight-drenched classrooms progress faster in maths and reading than do those in darker ones 5 .…”
Section: Living In the Labmentioning
confidence: 99%
“…Food environment [109][110][111] Unsafe recreation and living areas [112][113][114][115] Unwholesome foods [116] Low ambient temperature [117][118][119] Food deserts [120,121] Obesogenic chemicals such as endocrine disruptors (Bisphenol A, phthalates, atrazine, organotins and perfluorooctanoic acid) [122,123] Obesogenic foods/living in food swamps [124] Dysfunction of appetite and satiety centers in brain [137] Dysfunction of frontal cortex of brain that controls impulsive eating [138,139] Problem with brain neuro-transmitters [139,140] ADHD in children leading to adult obesity [141] General Prescription medications-side effects of commonly prescribed drugs (drugs for diabetes, hypertension, allergy contraception, corticosteroids & health issues) [142] Psychiatric Prescription Drugs -side effects (Prescription drugs-for mental health issues-schizophrenia , depression, anxiety, mood etc) , [134,136] …”
Section: Environmental Causes Of Obesity and Overweight Referencesmentioning
confidence: 99%
“…Unsafe recreation & living areas [112][113][114][115] c. Unwholesome foods [116] d. Low ambient temperature: Sometimes obesity could result from sitting for long time in low ambient temperatures. Several reports have implicated sedentary lifestyle in air conditioned environment in the cause of obesity [117][118][119].…”
Section: Lifestyle and Behaviour Related Factors That Cause Obesmentioning
confidence: 99%